Answer:
157
Step-by-step explanation:
You don't need to do any multiplication here. It is a fundamental addition problem.
It is given that Lori has got 91 apples and Jay has got 68 of them. We have to find how many apples do they have together.
The correct solution is to add the numbers together:
91+68=157 apples
Answer:;4.4
Step-by-step explanation: Since it varies inversely we know G times H squared is equal to some constant, k. So we have G*H*H=k. We are told that when H=4, G=.25. Plugging this in, we have .25*4*4=k. This simplifies to 4=k. Our new equation is G*H*H=4. Now, we want to solve for G when H=.3. We plug it in. G*.3*.3=4 => G*.09=4. G=4/.09. This means G is approximately 44.4.
First, find out what the greatest common factor is between 2, 4, and 5.
<span>This is 20. So any number divisible by 20 is also divisible by 2, 4, and 5. </span>
<span>Now we find the list of numbers that are multiples of 20 between 67 and 113. </span>
<span>The solutions are: </span>
<span>80 and 100.</span>
Problem 11
<h3>Answer: h =
2A/b</h3>
------------------
Explanation:
We need to get h by itself. To do so, we first multiply both sides by 2. Then we divide both sides by b
A = (1/2)*b*h
2A = b*h
b*h = 2A
h = 2A/b
================================================
Problem 12
<h3>Answers:</h3>
- Equation: (n+2)/5 = 14
- Solution to that equation: n = 68
------------------
Explanation:
The number n is increased by 2 to get n+2
Then we divide by 5 to get (n+2)/5
This is set equal to 14 to get the equation (n+2)/5 = 14
Solving the equation would look like this
(n+2)/5 = 14
n+2 = 5*14 .... multiply both sides by 5
n+2 = 70
n = 70-2 .... subtract 2 from both sides
n = 68
================================================
Problem 13
<h3>Answer: Not a solution</h3>
------------------
Explanation:
We'll replace every copy of x with -3 and simplify
-2x + 5 > 13
-2*(-3) + 5 > 13
6 + 5 > 13
11 > 13
The last inequality is false because 11 is not greater than 13. Since the last inequality is false, this makes the first inequality false when x = -3.
Therefore, x = -3 is not a solution.